Community perceptions of protective practices to prevent ash exposures around Sakurajima volcano, Japan. (June 2020) - Covey, J.; Horwell, C.J.; Ogawa, R.; Baba, T.; Nishimura, S.; Hagino, M.; Merli, C.
Abstract: Whilst, globally, volcanic eruptions are unusual and cause anxiety in affected communities, people living near Sakurajima volcano, Japan are exposed to frequent ashfall with little-to-no official intervention. As part of a wider project, this study assessed how this apparently normalised experience affects residents' perceptions of health impacts, and whether it is important to protect themselves from ash inhalation. A survey of 749 residents found little evidence of normalisation. Respondents identified a range of symptoms (including eye irritation, low mood, sore throat, cough) perceived to be associated with ash exposure, with 67% experiencing at least one symptom. Only 6% of respondents thought it was not important to protect themselves, and path analysis showed that protection was particularly important to older people and those with existing respiratory disease, who were more likely to rate ash as harmful or associate symptoms with exposures. Therefore, some of the most vulnerable sectors of this community are adversely impacted by ash. However, despite the local government recommending protective measures, most respondents said they had not received advice, but would like to. They took actions that they thought were effective (keeping windows/doors closed) or were easily available (wearing surgical masks). Other research has shown that industry-certified (e.g., N95) masks are more effective than surgical masks. Here, respondents recognised this, but high-efficiency masks were rarely used, probably due to unavailability. The results demonstrate a need to provide ash-affected communities with targeted, evidence-based information on options for effective protection, coupled with ensuring that communities have access to suggested interventions.